Genetic variation in interleukin-28B predicts SVR in hepatitis C genotype 1 Argentine patients treated with PEG IFN and ribavirin - Ridruejo, Ezequiel (2011)
BACKGROUND AND AIMS: Genetic variations in the interleukin 28B (IL28B) gene have been associated with viral response to PEG-interferon-α/ribavirin (PR) therapy in hepatitis C virus (HCV) genotype 1 infected patients from North America, Europe and Asia. The importance of these IL28B variants for Argentine patients remains unknown. MATERIAL AND METHODS: IL28B host genotypes (rs8099917 and rs12979860) were determined in a population of Argentine patients with European ancestry. Results were analyzed looking for their association with sustained virologic response (SVR) to PR therapy and compared with other baseline hosts' biochemical, histological and virological predictors of response. RESULTS: We studied 102 patients, 60% were men, and 40% of them were rs8099917 TT and 18% rs12979860 CC. Mean baseline serum HCV RNA was 1.673.092 IU/mL and mean F score was: 2.10 ± 1.18 (21% cirrhotic). SVR rate was higher in rs8099917 TT genotypes (55%) when compared to GT/GG (25%) (p = 0.002) and in rs1512979860 CC (64%) than in CT/TT (30%) (p = 0.004). The univariate analysis showed that rs8099917 TT (OR 3.7; 95 %CI 1.5-8.7; p = 0.002), rs12979860 CC (OR 4.6; 95%CI 1.5-13.7; p = 0.006), low viral load (OR 4.6; 95% CI 1.7-12.6; p = 0.002) and F0-2 (OR 8.5; 95% CI 2.3-30.6; p = 0.001) were significantly associated with SVR. In the multivariate analysis, rs12979860 CC, rs8099917 TT, viral load < 400.000 IU/mL and F0-2 were associated with SVR rates (p = 0.029, p = 0.012, p = 0.013 and p = 0.004, respectively). CONCLUSION: IL28B host genotypes should be added to baseline predictors of response to PR therapy in Latin American patients with European ancestry.